Penerapan Pembelajaran Berbasis Teknologi dengan Menggunakan Multimedia dalam Pembelajaran PAI di SD Kradenan 01 Kota Pekalongan - Louis, M. Ariel Ramadhan (TSAQOFAH, 2023)
PAI material is one of the scientific disciplines that will enable students to know their obligations towards the Khaliq, so that Islamic Religious Education is taught not limited to mastering a collection of knowledge, in the form of facts, concepts or principles only, but learning Islamic Religious Education must also be able to produce students who are able to carry out and apply their knowledge. The problem formulation of this research is to obtain results from the use of multimedia in PAI learning at SDN Kradenan 01 Pekalongan City. Aims to reveal how Islamic religious education teachers utilize information and communication technology media in the form of computer multimedia in learning. The research method used is descriptive qualitative, research sources consist of events, teachers and several students selected purposively, data is obtained through observation, interviews and documentation studies, the data that has been collected is then analyzed using an interactive approach. The results of the research show that the principal determines ICT-based learning by using various kinds of multimedia tools in each lesson, PAI teachers carry out ICT-based PAI learning planning using multimedia tools, evaluation of the use of multimedia computers in PAI learning is carried out by PAI teachers themselves to find deficiencies. implementation of learning using multimedia computers. The conclusion that PAI teachers at SDN Kradenan 01 get is using multimedia-based ICT strategies in their learning process.